Standards, legislation and other requirements concerning the design of the fuel gas system in power plants - Hanka, Juuso (My University, 2019)
Legislative requirements have impacted the current design of the fuel gas system. There is no consensus on how well it supports to Wärtsilä’s product portfolio. Different parts of the world have different requirements for gaseous fuel systems. These requirements must be fulfilled when designing the fuel gas system. The aim of this study was to examine the requirements of different countries’ standards and legislation for the gas system in Wärtsilä’s market areas. Another objective was to examine the engine requirements for the gas supply system. The first part of the study consists of a review of the current Wärtsilä gaseous fuel ancillary system. In the second part of the thesis, the current standards, directives, and legislation that influences the design of the current system are reviewed. In the final parts of the thesis, the legal requirements of two different countries for the design of the gaseous fuel system were investigated. Also, the requirements of the system from the engine perspective was investigated. Considering the design of the fuel gas systems, it is crucial for Wärtsilä to modify the design according to the standards in their target country because they differ from the standards and legislation used in the EU. Although there are some similarities with the EU standards, they do vary depending on the target country. They have different definitions and classifications. Considering the new engine models, the ancillary system must also be compatible with the requirements of the engine. The thesis resulted in a preliminary picture of standards and legislation in two different countries, which influences the design of the fuel gas system. In addition, the requirements of two different engine types for the design of the fuel gas system were defined.
Keywords: Gas; fuel gas system; ancillary system; standard; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|